Education and training in breast care for postpartum mothers during the Covid-19 pandemic - Marieta Kristina Sulastiawati Bai; Raimuda Woga; Rifatunnisa Rifatunnisa (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Breast care is an activity carried out consciously to maintain breast health during pregnancy and after childbirth in order to prepare for lactation during the postpartum period. Based on a preliminary survey conducted at Ende General Hospital in November 2021, it was found that many mothers were still not skilled in breast care. Purpose: To determine the effect of breast care training on breast care skills for postpartum mothers during the Covid-19 pandemic. Method: One Group pretest posttest design, sample selection using purposive sampling technique. The sample obtained was 16 participants. The instrument used in the study was a checklist. The data was then analyzed using univariate analysis which processed the data results in the form of percentages and bivariate analysis using the Wilcoxon test. Results: Skills before the intervention participants when performing breast care can mostly perform breast care with assistance as many as 9 (56.3%), and after the intervention most participants can perform breast care independently as many as 11 (68.8%). Conclusion: There is an effect of breast care training on breast care skills in postpartum mothers at Ende Regional Hospital in 2022. Suggestion: Health workers should improve plans or promotions about the importance of breast care which is useful for increasing breast milk production so that it can help the success of the government program in efforts to provide exclusive breastfeeding.